An analysis of the flood management and mitigation measures in Zimbabwe for a sustainable future. (October 2018) - Samu, Remember; Kentel, Aysu Sagun
Abstract: Floods have prevailed in the recent years, hampering not only social but also the economic development as well. This global pandemic has caused loss of lives, property and economic damages in many countries, including Zimbabwe. Rainfall intensity in the country's seven main river catchments namely; Mzingwane, Gwayi, Save (or Sabi), Mazowe (or Mazoe), Sanyati, Manyame and Runde triggers flash floods due to high peak discharges. It is therefore of paramount importance to try and reduce or rather prevent these losses due to flood events. The main objective of this study is to ascertain flood events in Zimbabwe and discuss how best they can be managed for a sustainable future. The assessment is carried out using AQUEDUCT Global Flood Analyzer in which all the analysis is based on the Gross Domestic Product (GDP), population and the present and future (2030) urban damage. To estimate future changes and effectively suggest flood disaster management and mitigation strategies, three scenarios obtained from the Intergovernmental Panel on Climate Change 5th Assessment Report were utilized. A 5-year flood protection was then employed and the urban damage due to the flood events, the population at risk and the effects of this disaster on GDP was determined. This study outlined that in any given year, the majority of Zimbabwe has a low to a medium that is 2–3% probability of flood occurrence in which a 5-year flood has a 20% occurrence probability in any given year. If there is no flood protection employed, this 5-year flood could cause 106.3 thousand affected population, 32.4 million urban damage and 67.9 million affected GDP. It is concluded that it is impossible to completely eliminate flood events, however, proposed mitigation measures, diminution approach and proper planning and preparation before their occurrence can reduce the environmental, economic and social losses.